A literature review on the causal relationship between Occlusal Factors (OF) and Temporomandibular Disorders (TMD) V: effect of changes in occlusal factors achieved with orthodontic treatment - Acosta-Ortíz, Rodolfo; Rojas-Sarria, Blanca Patricia (Revista Facultad de Odontología Universidad de Antioquia, 2011)
Introduction: this is the fifth article in this series, which aims to present a literature review regarding the causal relationship between occlusal factors (OF) and temporomandibular disorders (TMD). Methods: This article presents and analyzes epidemiological reports (cross-sectional and analytical) in which the relationship between orthodontic treatment (OT) and TMD was studied. Results: most of the reports (70%) did not support any association between OT and TMD development. Conclusion: even though the general tendency was the lack of association between OT and TMDs throughout different reports, perhaps in the future, an improvement in the research design will allow obtaining more concrete results that can help us reach a solid interpretation about the relationship between OT and TMDs. Other factors, such as genetics, may play a role as confounding variables and should be studied and considered in the etiology, prevention, or management of TMDs. Apart from the possible relationship between OT and TMDs, an important clinical recommendation is to carry out the appropriate TMD screening in patients who will receive an OT.